RIPK1 and RIPK3 inhibitors: potential weapons against inflammation to treat diabetic complications - Ke, Dan; Zhang, Zhen; Liu, Jieting; Chen, Peijian; Dai, Yucen; Sun, Xinhai; Chu, Yanhui; Li, Luxin (Frontiers in Immunology, 2023)
Diabetes mellitus is lifelong metabolic diseases that are characterized by chronic hyperglycemia due to a variety of etiological factors. Long-term metabolic stress induces harmful inflammation leading to chronic complications, mainly diabetic ophthalmopathy, diabetic cardiovascular complications and diabetic nephropathy. With diabetes complications being one of the leading causes of disability and death, the use of anti-inflammatories in combination therapy for diabetes is increasing. There has been increasing interest in targeting significant regulators of the inflammatory pathway, notably receptorinteracting serine/threonine-kinase-1 (RIPK1) and receptor-interacting serine/threonine-kinase-3 (RIPK3), as drug targets for managing inflammation in treating diabetes combinations. In this review, we aim to provide an up-to-date summary of current research on the mechanism of action and drug development of RIPK1 and RIPK3, which are pivotal in chronic inflammation and immunity, in relation to diabetic complications which may be benefit for explicating the potential of selective RIPK1 and RIPK3 inhibitors as anti-inflammatory therapeutic agents for diabetic complications.